Combination Procedure for Acne Scars Revision, Is It Needed? - Utama, Redha Cipta; Yenny, Satya Wydya; Norawati, Lilik; Arimuko, Abraham (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: The treatment of acne scars is a problem for dermatologist. Varied morphology of acne scars makes the treatment more difficult. Combination technique has high efficacy than monotherapy. The challenge is how to select best combination procedure for scar revision. Case presentation: A 43-year-old male present with acne scars since 5 years ago. Dermatological findings revealed atrophic acne scars (ice pick, boxcar, rolling) types on forehead, nose and cheeks. Diagnosis established as moderate atrophic acne scars with global acne scarring system (GASS) is 21. Patient treated with blunt canula subcision, hyaluronic acid (HA) filler, microneedling radiofrequency, 90% trichloroacetic acid chemical reconstruction of skin scars (TCA CROSS) and application of salmon polydeoxyribonucleotide (PDRN). Patient also received topical 0.05% retinoic acid, 4% niacinamide, and sunscreen for daily. After 10 days, there is flattening and disappear of ice pick and boxcar, elevating of rolling scar, GASS score is 15. Blunt cannula subcision and HA filler is safe, effective for rolling scar through fibrous band breaking and prevent re-adhesion. Microneedling RF is effective for boxcar, otherwise 90% TCA CROSS preferrable for ice pick scars. This combination procedure leading cellular necrosis in epidermis, collagen in dermis, and stimulate regeneration. Application of Salmon PDRN may promote wound healing, hydrate the epidermis, and prevent dyschromia. Conclusion: Combination of subcision, dermal filler, microneedling radiofrequency, 90% TCA CROSS, and Salmon PDRN has high efficacy for scar revision through collagen remodelling and acceleration wound healing.